Oral anticoagulant management of patients with mechanical heart valves at the Salam Centre of Khartoum: Observations on quality of anticoagulation and thrombotic risk. Issue 219 (November 2022) - Erba, Nicoletta; Tosetto, Alberto; Langer, Martin; Abdallah, Suha Abdelwahab; Giovanella, Elena; Lentini, Salvatore; Masini, Franco; Mocini, Alessandro; Portella, Gennarina; Salvati, Alessandro Cristian; Squizzato, Alessandro; Testa, Sophie; et al.
Abstract: Introduction: Rheumatic heart disease with mechanical heart valve (MHV) replacement is common in Africa. However, MHV requires long-life anticoagulation and managing this can be challenging. Methods and results: We report data of a prospective observational study conducted between August 2018 and September 2019 in MHV patients in the Salam Centre for Cardiac Surgery built in Khartoum, by Emergency, an Italian Non-Governmental Organization, to evaluate the quality of anticoagulation control and the risk of thrombotic complications. Results: We studied 3647 patients (median age 25.1 years; 53.9 % female). Median Time in Therapeutic Range (TTR) was 53 % (interquartile range 37 % to 67 %) and 70 thrombotic events (rate 1.8 × 100 pt-years [95 % CI 1.38–2.23]) were recorded. Among patients in the first quartile of TTR (≤37 %), we recorded 34/70 (48.6 %) of all thrombotic events (rate 3.7 × 100 pt-years [95 % CI 2.5–5.1]), with a high mortality rate (2.2 × 100 pt-years [95 % CI 1.3–3.3]). In patients with guideline-recommended TTR (≥65 %) the event rate was 0.8 × 100 pt-years for thrombotic events [95 % CI 0.3–1.5] and 0.4 × 100 pt-years for mortality [95 % CI 0.1–0.9]. Multivariable analysis showed that having a TTR in the lowest quartile (≤37 %) and being noncompliant are significantly associated with increased thrombotic risk. Aspirin use or different valve type did not influence the thrombotic risk. Almost 40 % of all thromboembolic complications could have been potentially prevented by further improving VKA management to obtain a TTR > 37 %. Conclusion: The thrombotic risk of MHV patients on VKAs living in a low-income country like Sudan is associated with low quality of anticoagulation control. Efforts should be made to decrease the number of non-compliant patients and to reach a guideline-recommended TTR of ≥65 %.